Accounting for sustainability - Rimmel, Gunnar (Routledge, 2026)
This book provides a broad overview of how sustainability reporting has grown, how it is used now, and where it is heading.Daily, we encounter concepts such as corporate social responsibility (CSR); sustainability reporting; sustainability accounting; environmental reports; corporate citizenship or environmental management systems; or Environmental, Social and Governance (ESG) disclosures. Accounting for Sustainability decodes this terminology by offering an accessible introduction that explores sustainability reporting from both internal and external perspectives. It begins with an overview of key terms and theories, followed by chapters on financial management, sustainability standards, accounting communication, and capital markets. This new edition has been fully revised and expanded with four new chapters, including coverage of the EU's Corporate Sustainability Reporting Directive (CSRD), European Sustainability Reporting Standards (ESRS), and the global efforts of the International Sustainability Standards Board (ISSB). It also includes critical reflections on digitalisation, standard-setting, and assurance.With learning outcomes and study questions embedded in each chapter, this book will be of great interest to students of sustainability reporting and accounting, as well as practitioners taking related professional accreditations.